Evolution of the concept of terrorism in criminal legislation - Shirshov, Alexey A.; Korobeev, Alexander I.; Hung, Nguyen (Opción, 2019)
This paper analyzes the trends in the criminal legislation of the Socialist Republic of Vietnam in terms of responsibility for terrorist crimes. As a method, the authors characterize the specific features of the development of the criminal law of the SRV and analyze the reasons for changing the legislative paradigm in the definition of terrorism in the Criminal Code of the SRV. In result, the norms of international conventions on combating terrorism have been implemented in the national legislation of the Socialist Republic of Vietnam. In conclusion, religious conflicts in modern Vietnam are virtually a nonsense.